How to estimate age of old bottlenose dolphins (Tursiops truncatus); by tooth or pectoral flipper? - Barratclough, Ashley; McFee, Wayne E.; Stolen, Megan; Hohn, Aleta A.; Lovewell, Gretchen N.; Gomez, Forrest M.; Smith, Cynthia R.; Garcia-Parraga, Daniel; Wells, Randall S.; Parry, Celeste; Daniels, Risa; Ridgway, Sam H.; et al. (Frontiers in Marine Science, 2023)
Multiple techniques have been used for estimating age in bottlenose dolphins (Tursiops truncatus). The longest established technique is via counts of growth later groups (GLGs) in the longitudinal section of an extracted mandibular tooth. Previous studies to validate GLGs have primarily used younger dolphins (less than 16yrs old) due to the limited number of known age older animals. This study assessed the accuracy of age estimates for bottlenose dolphins using both GLG analysis and a newer technique, pectoral flipper radiography (PFR) for dolphins ranging from 0 to 58yrs, with a majority of samples (70%) over 16yrs. GLGs were assessed by two expert independent readers on tooth sections from 52 different dolphins (85% over 16yrs, maximum age 58yrs), and assessments of PFRs were performed by two experienced veterinarians on 37 dolphins (54% over 16yrs, maximum age 54yrs). Results demonstrated both techniques became less accurate in older dolphins, particularly those > 30yrs, with errors as large as 37yrs for GLG estimates. The root mean squared error (RMSE) for age estimation using GLGs for dolphins ≤15 years of age was 1.46yrs compared to 1.58yrs using PFRs demonstrating the accuracy of both techniques in this age bracket. For dolphins >30yrs, RMSE increased to 17yrs in GLG aging and 8.25yrs in PFR. Challenges in obtaining accurate age estimates in GLGs were primarily due to sectioning and staining difficulties in visualizing the newest GLG layers, in the very old animals. Complications in reading the layers included obtaining a good section, the presence of accessory layers, GLG compression, and tooth curvature or wear removing the neonatal line influencing aging biases. In pectoral flipper aging, the primary challenge was obtaining a true dorsoventral radiograph in a live dolphin during a health assessment, as well as the subjective assessment of scoring and reliance on degenerative changes accurately estimate age in geriatric dolphins. While access to the radiography equipment can be a limiting factor, the improved accuracy for age estimation in adult dolphins, the less invasive nature, and reduced processing time to results make pectoral radiography a preferred alternative technique for estimating age in live dolphins.